A Comparison of Two Methods for MRI Classification of At-Risk Tissue and Core Infarction - Leigh, Richard; Urrutia, Victor C.; Llinas, Rafael H.; Gottesman, Rebecca F.; Krakauer, John W.; Hillis, Argye E. (Frontiers in Neurology, 2014)
Objective: To compare how at-risk tissue and core infarction were defined in two major trials that tested the use of MRI in selecting acute stroke patients for endovascular recanalization therapy. Methods: MRIs from 12 patients evaluated for possible endovascular therapy were processed using the methods published from two major trials, MR RESCUE and DEFUSE 2. Specifically, volumes of at-risk tissue and core infarction were generated from each patient’s MRI. MRIs were then classified as to whether or not they met criteria for salvageable tissue: “penumbral pattern” for MR RESCUE and/or “target profile” for DEFUSE 2) as defined by each trial. Results: Volumes of at-risk tissue by the two definitions were correlated (p=0.017) while the volumes of core infarct were not (p=0.059). The volume of at-risk tissue was consistently larger when defined by the penumbral pattern than the target profile while the volume of core infarct was consistently larger when defined by the target profile than the penumbral pattern. When these volumes were used to classify the MRI scans, nine out of 12 patients (75%) were classified as having a penumbral pattern, while only 4 out of 12 patients (33%) were classified as having a target profile. Of the 9 patients classified as penumbral pattern, 5 (55%) were classified differently by the target profile. Interpretation: Our analysis found that the MR RESCUE trial defined salvageable tissue in a way which made it more likely for patients be labeled as favorable for treatment. For the cohort of patients examined in this study, had they been enrolled in both trials, most of the patients identified as having salvageable tissue by the MR RESCUE trial would not have been considered to have salvageable tissue in the DEFUSE 2 trial. Caution should be taken in concluding that MRI selection for endovascular therapy is not effective as imaging selection criteria were substantially different between trials.